ANALISIS KINERJA KEUANGAN PT. PAPUA TV DI JAYAPURA - Risky Novan Ngutra; Elsyan Rienette Marlissa (Universitas Cenderawasih, 2017)
Research Objective to find out how much capital capability of PT.Papua TV. Jayapura., How much management ability of PT.Papua TV. Jayapura. How much acceptance ability of PT. Papua TV. Jayapura. How much Comparison of Operational Cost to Operating Income (BOPO) from PT.Papua TV. Jayapura. And How much Loan to Deposit Ratio (LDR) from PT.Papua TV. Jayapura. The method used is Camel model analysis using data of period 2010-2013. TV Health Level Analysis Results. Papua based on Camel Model that is (1). Capital Adequacy Ratio (CAR) approach for 2011 through 2013 Healthy Capital of Papua TV Capital (2) Net Profit Margin (NPM) approach, 2011 to 2013 Healthy Papua TV financial management (3) Return on Asset (ROA) , the financial condition of Papua TV in 2013 is healthy because the assets in question are still greater than the profit. (4) The Operational Cost Approach to Operational Income BOPO.Tahun 2013 BOPO Papua TV is 332.6 bigger than 95.92% which means the oparasional cost (5) Loan to Deposit Ratio (LDR) explains that the financial condition of Papua TV can not be measured healthy category or unhealthy because of PT. Papua TV is not a BUMD engaged in credit so that for LDR analysis can not be measured. Keywords: Financial performance, capital capability, management, revenue, and Operating Income